2017
DOI: 10.3390/toxins9010025
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Indoxyl Sulfate on Progenitor Cell-Related Neovascularization of Peripheral Arterial Disease and Post-Angioplasty Thrombosis of Dialysis Vascular Access

Abstract: Patients with chronic kidney disease (CKD) have an increased risk of vascular disease, which is associated with considerable health care costs. Vascular disease in CKD differs clinically and pathobiologically from that in patients with normal renal function. Besides the traditional risk factors, retention of uremic toxins contributes to the pathogenesis of vascular disease in patients with CKD. Indoxyl sulfate is a protein-bound uremic toxin and is inefficiently removed by conventional dialysis. Accumulating e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…27, 36 Finally, neovascularization has been reported to play an important role in the pathophysiology of AAA, 37 and given that CKD is a clinical phenotype of microvascular disease, it is possible that those with CKD are more likely to have abnormal aortic neovascularization compared to those without CKD. 38 Nonetheless, future studies are needed to explore these and other pathophysiological mechanisms, which may link CKD, particularly albuminuria, to AAA.…”
Section: Discussionmentioning
confidence: 99%
“…27, 36 Finally, neovascularization has been reported to play an important role in the pathophysiology of AAA, 37 and given that CKD is a clinical phenotype of microvascular disease, it is possible that those with CKD are more likely to have abnormal aortic neovascularization compared to those without CKD. 38 Nonetheless, future studies are needed to explore these and other pathophysiological mechanisms, which may link CKD, particularly albuminuria, to AAA.…”
Section: Discussionmentioning
confidence: 99%
“…According to data provided by Ahmed et al, IS can trigger RBCs shrinkage and RBCs cell membrane scrambling that lead to suicidal erythrocyte death, which can impede microcirculation [ 13 ]. Furthermore, IS impairs endothelial progenitor cells, which lack is connected with thrombotic events after endovascular interventions [ 15 , 16 ]. In recent times, higher level of IS was connected with increased risk for dialysis graft thrombosis and associated with higher number of thrombectomy procedures [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with CKD, the accumulation of uremic toxin disrupted EPC migration into the endothelium. Wu et al demonstrated that the protein-bound uremic toxin indoxyl sulfate down-regulated endothelial vacuolization by disrupting the effect of HIF-1-alpha [13]. Thus, indoxyl sulfate disrupted EPCs regeneration and endothelial repair.…”
Section: Epcs and Arterial Calcificationmentioning
confidence: 99%
“…EPCs originating from the bone marrow were shown to be an important mechanism in the repair of injured endothelial cells [12]. However, the EPC phenotype was altered under specific pathologic states, such as the accumulation of uremic toxins [13]. The EPCs with osteogenic character were related to the severity of the vascular calcification [14], and the pharmacologic dose of active vitamin D supplement might enhance the expression of calcifying EPCs in CKD patients [15].…”
Section: Introductionmentioning
confidence: 99%